2014
DOI: 10.1111/cea.12383
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an epithelial barrier protective cationic aerosol on allergen‐induced airway inflammation in asthma: a randomized, placebo‐controlled clinical trial

Abstract: Inhaled cationic airway lining modulator (iCALM) is a cationic aerosol therapy comprised of 1.29% calcium chloride dissolved in 0.9% isotonic saline that enhances the biophysical barrier function of the airway lining fluid and primes the host defense response. It's ability to attenuate bronchitis caused by inhaled particles was investigated using an allergen-inhalation model in a proof-of-concept study. In a randomized, double-blind, placebo-controlled cross-over trial of 6 mild atopic steroid-naïve asthmatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Although anti-IL-5 antibodies have been reported to effectively reduce eosinophil levels in the circulation and airways, one study of treatment with anti-IL-5 did not show any inhibition of the LAR but did markedly attenuate allergen-induced airway eosinophilia (table 2) [57]. However, blocking receptors Calcium channel blocker [145] Cationic airway lining modulator [146] Heparin disaccharide [147] Cromones [148,149] Nonsteroidal anti-inflammatory drug [129,150] Lysine ASA [151] Synbiotics [152] ω-3 polyunsaturated fatty acids [153] Furosemide [103] CS: corticosteroid; CytLT: cysteinyl leukotriene; NK: neurokinin; COX: cyclo-oxygenase; MAb: monoclonal antibody; IL: interleukin; TSLP: thymic stromal lymphopoietin; PDE: phosphodiesterase; CRTH2: chemoattractant receptor-homologous molecule expressed on type 2 helper T-cells; IL-4R: IL-4 receptor; VLA: very late antigen; TNF: tumour necrosis factor; Bc: common β-chain; PPAR: peroxisome proliferator-activated receptor; ASA: acetylsalicylate.…”
Section: Allergen Inhalation Challenge To Study New Drugs For Asthmamentioning
confidence: 99%
“…Although anti-IL-5 antibodies have been reported to effectively reduce eosinophil levels in the circulation and airways, one study of treatment with anti-IL-5 did not show any inhibition of the LAR but did markedly attenuate allergen-induced airway eosinophilia (table 2) [57]. However, blocking receptors Calcium channel blocker [145] Cationic airway lining modulator [146] Heparin disaccharide [147] Cromones [148,149] Nonsteroidal anti-inflammatory drug [129,150] Lysine ASA [151] Synbiotics [152] ω-3 polyunsaturated fatty acids [153] Furosemide [103] CS: corticosteroid; CytLT: cysteinyl leukotriene; NK: neurokinin; COX: cyclo-oxygenase; MAb: monoclonal antibody; IL: interleukin; TSLP: thymic stromal lymphopoietin; PDE: phosphodiesterase; CRTH2: chemoattractant receptor-homologous molecule expressed on type 2 helper T-cells; IL-4R: IL-4 receptor; VLA: very late antigen; TNF: tumour necrosis factor; Bc: common β-chain; PPAR: peroxisome proliferator-activated receptor; ASA: acetylsalicylate.…”
Section: Allergen Inhalation Challenge To Study New Drugs For Asthmamentioning
confidence: 99%
“…PET analysis of beta-amyloid and tau burden). For example, eotaxin-1/CCL11 has been used as a biomarker in clinical trials in asthma ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other trials have also investigated the potential of enhancing the epithelial barrier to reduce airway inflammation caused by inhaled particles. For instance, a cross‐over double‐blind, randomized controlled trial involving six mild atopic steroid‐naïve asthmatic subjects demonstrated that three doses of an inhaled cationic airway lining modulator had well‐tolerated effects, resulting in attenuation of allergen‐induced sputum eosinophils and reduction of IL‐5, MCP‐1, and eotaxin levels 10 . Moreover, a separate study identified the human CST1 protein as an inhibitor of allergenic protease activity, effectively safeguarding the bronchial epithelial barrier in individuals with asthma, and suggesting CST1 as a promising biomarker for asthma control 11 …”
Section: Figurementioning
confidence: 99%